PENGARUH FAKTOR SOSIAL EKONOMI DAN ASURANSI BPJS PASIEN TERHADAP KEPUASAN PASIEN YANG DIMODERASI KUALITAS PELAYANAN DI PUSKESMAS BITTUANG KECAMATAN BITTUANG KABUPATEN TANA TORAJA - Rustan, Sriwahyuni; Muhardi, Muhardi; Perkasa, Subhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
This study aims to determine the influence of socio-economic factors and patient BPJS insurance on service quality and patient satisfaction at the Bittuang Health Center, Bittuang District, Tana Toraja Regency. This research is a type of quantitative descriptive research. The population of this study were patients at the Bittuang Health Center, Bittuang District, Tana Toraja Regency and a sample of 170 respondents. Types of data collection using questionnaires, observation and documentation. Data analysis using multiple regression method. The results of this study indicate that socio-economic factors affect the quality of service at the Bittuang Health Center, Bittuang District, Tana Toraja Regency. BPJS insurance has a positive effect on the quality of service at the Bittuang Health Center, Bittuang District, Tana Toraja Regency. Socio-economic factors affect patient satisfaction at the Bittuang Health Center, Bittuang District, Tana Toraja Regency. And BPJS Insurance has a positive effect on patient satisfaction at the Bittuang Health Center, Bittuang District, Tana Toraja Regency.